The investment activity of companies in Poland by industry = Aktywność inwestycyjna przedsiębiorstw w Polsce - ujęcie branżowe - Jędrzejczak-Gas, Janina; Barska, Anetta; Bánociová, Anna (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this article is to assess the investment activity (investing activities) of companies in Poland depending on the industry they belong to. The first part of the study presents theoretical issues concerning business investments. The second part presents a comparative study of the investment activity of Polish companies operating in various industries. In this study, in order to assess the investment activity of companies in Poland based on the industry they belong to, two selected methods of linear ordering (the method of sums and Hellwig's method) were used, both falling within the scope of a multidimensional comparative analysis.
Keywords: działalność inwestycyjna; miara syntetyczna; analiza porównawcza; investment activity; synthetic measure; comparative analysis